2018
DOI: 10.1039/c8ra02827c
|View full text |Cite
|
Sign up to set email alerts
|

2,3-Dihydroquinazolin-4(1H)-one as a privileged scaffold in drug design

Abstract: 2,3-Dihydroquinazolin-4-one (DHQ) belongs to the class of nitrogen-containing heterocyclic compounds representing a core structural component in various biologically active compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(66 citation statements)
references
References 308 publications
0
56
0
3
Order By: Relevance
“…[16] All three MOFs were found to be capable of catalyzing the cascade reaction, whereas 1 gave much higher reactivity and stereoselectivity than 2 and 3.I np articular, after screening av ariety of reaction conditions such as catalyst loading,r eaction time,t emperature,a nd solvents,i t was found that, with 5mol %l oading, 1 could catalyze the reaction of benzaldehyde and 2-aminobenzamide to the desired 2,3-dihydroquinazolinone in 96 %y ield and 99 % ee in CHCl 3 at 80 8 8Ca fter 20 h( Table 1, 4a). [16] All three MOFs were found to be capable of catalyzing the cascade reaction, whereas 1 gave much higher reactivity and stereoselectivity than 2 and 3.I np articular, after screening av ariety of reaction conditions such as catalyst loading,r eaction time,t emperature,a nd solvents,i t was found that, with 5mol %l oading, 1 could catalyze the reaction of benzaldehyde and 2-aminobenzamide to the desired 2,3-dihydroquinazolinone in 96 %y ield and 99 % ee in CHCl 3 at 80 8 8Ca fter 20 h( Table 1, 4a).…”
Section: Heterogeneous Asymmetric Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…[16] All three MOFs were found to be capable of catalyzing the cascade reaction, whereas 1 gave much higher reactivity and stereoselectivity than 2 and 3.I np articular, after screening av ariety of reaction conditions such as catalyst loading,r eaction time,t emperature,a nd solvents,i t was found that, with 5mol %l oading, 1 could catalyze the reaction of benzaldehyde and 2-aminobenzamide to the desired 2,3-dihydroquinazolinone in 96 %y ield and 99 % ee in CHCl 3 at 80 8 8Ca fter 20 h( Table 1, 4a). [16] All three MOFs were found to be capable of catalyzing the cascade reaction, whereas 1 gave much higher reactivity and stereoselectivity than 2 and 3.I np articular, after screening av ariety of reaction conditions such as catalyst loading,r eaction time,t emperature,a nd solvents,i t was found that, with 5mol %l oading, 1 could catalyze the reaction of benzaldehyde and 2-aminobenzamide to the desired 2,3-dihydroquinazolinone in 96 %y ield and 99 % ee in CHCl 3 at 80 8 8Ca fter 20 h( Table 1, 4a).…”
Section: Heterogeneous Asymmetric Catalysismentioning
confidence: 99%
“…Second, ah ot filtration test showed no indication of catalysis by leached homogeneous species.I nductively coupled plasma optical emission spectrometry (ICP-OES) analysis of the product solution indicated almost no loss of In ions (ca. [16] It was found that 1 loading at 5mol % catalyzed the asymmetric condensation/amine addition reaction between 2-amino-5-nitrobenzamide and 2'-methylbiphenyl-4-carboxaldehyde in 95 %yield and 95 % ee. It should be noted that numerous Brønsted acid catalysts have been explored for the enantioselective synthesis of 2,3dihydroquinazolinone, [17] but in most cases,only moderate to excellent enantioselectivities were observed.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…52,53 Traditionally, both homogeneous and heterogeneous acidic catalysts can catalyze the synthesis of 2,3-dihydroquinazolin-4(1H)-ones. [54][55][56] Recently, various protocols have been reported for the preparation of 2,3-dihydroquinazolin-4(1H)-ones with the aid of improving the reaction efficiency. 57-61 Moreover, 2,3-dihydroquinazolin-4(1H)- .…”
Section: Synthesis Of 23-dihydroquinazolin-4(1h)-onesmentioning
confidence: 99%
“…20 There have been developed different methods of synthesis for 2,3-dihydroquinazolin-4(1H)-ones (DQZ) most recently; Mn III -based reaction, 21 under ultrasonic irradiation, 22 zeolite catalyzed method, 23 with green chemistry using nanoindium oxide 24 and carbon nanotubes as a heterogeneous catalyst, 25 etc. [26][27][28][29][30][31] QZ skeleton is very common in many natural alkaloids. [32][33][34] Keeping in view the above, we report a convenient and high yield eco-friendly synthesis of QZ using FeCl 3 /Al 2 O 3 as catalyst; FeCl 3 /Al 2 O 3 could be recovered and reused.…”
Section: Introductionmentioning
confidence: 99%